190 Translating Alzheimer’s Disease Research to Improve Dementia Screening Through Health Message Design in the Community: A Qualitative Study - Yolanda Jackson; Elizabeth K. Rhodus; Nancy G. Harrington (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: This study engaged Black adults who reside in a rural area of Kentucky to explore their beliefs, norms, knowledge, attitudes, and health-related behaviors about Alzheimer’s disease (AD) (RQ1) and what message elements are most relevant for designing a health message aimed at encouraging them to get screened for AD (RQ2). METHODS/STUDY POPULATION: This qualitative study was guided bythe Integrative Model of Behavior. Participants were recruited from a faith-based institution in rural Kentucky. Black adults aged 50+ years were invited to participate in the study, which consisted of two focus groups. Group 1 gained information about behavioral determinants (RQ1) and examined which message design elements were important to Black adults by asking for feedback on a handout from the Alzheimer’s Association that encouraged AD screening (RQ2). The handout was redesigned based on feedback from Group 1. Group 2 was involved in a discussion of the redesigned handout, asking for further feedback. Focus groups were audio recorded and transcribed verbatim. Data analysis included thematic analysis of transcripts of the focus groups and quantitative analysis. RESULTS/ANTICIPATED RESULTS: Participants (N=18) were all female and Black with a mean age of sixty-two years. For RQ1, Results revealed that 1) limited knowledge of AD led to feelings of not being able to do anything about the disease, whereas awareness and education led to hope; 2) past healthcare experiences informed subsequent beliefs and behaviors, and 3) culture impacted beliefs, with a cultural norm of “what happens in our house, stays in our house” being prominent. For RQ2, results revealed the importance of regionally specific messaging for AD. Generic statements that applied broadly did not appeal to participants. Message delivery, layout, and format for low literacy individuals are key for maximizing audience impact. Pictures give hints about the message and aid in understanding. DISCUSSION/SIGNIFICANCE: Barriers such as past experiences, lack of knowledge, and cultural norms negatively impact the likelihood that Black adults will get screened for AD, resulting in delayed healthcare or healthcare avoidance. Regionally specific health messaging for AD has the potential to encourage modifications in health-related behaviors.